Inhibition of macrophage‐derived foam cell formation by ezetimibe via the caveolin‐1/MAPK pathway. (February 2016) - Qin, Li; Yang, Yun‐Bo; Yang, Yi‐Xin; Zhu, Neng; Liu, Zheng; Ni, Ya‐Guang; Li, Shun‐Xiang; Zheng, Xi‐Long; Liao, Duan‐ Fang
Summary: Ezetimibe, a selective inhibitor of intestinal cholesterol absorption, effectively reduces plasma cholesterol, but its effect on atherosclerosis is unclear. Foam cell formation has been implicated as a key mediator during the development of atherosclerosis. The purpose of this study was to investigate the effects of ezetimibe on foam cell formation and explore the underlying mechanism. The results presented here show that ezetimibe reduces atherosclerotic lesions in apolipoprotein E deficient (apoE‐/‐) mice by lowering cholesterol levels. Treatment of macrophages with Chol:M β CD resulted in foam cell formation, which was concentration‐dependently inhibited by the presence of ezetimibe. Mechanically, ezetimibe treatment downregulated the expression of CD36 and scavenger receptor class B1 (SR‐B1), but upregulated the expression of apoE and caveolin‐1 in macrophage‐derived foam cells, which kept consistent with our microarray results. Moreover, treatment with ezetimibe abrogated the increase of phospho‐extracellular signal regulated kinase (ERK) 1/2 and their nuclear accumulation in foam cells. Inhibition of the MAPK pathway by the MEK inhibitor PD98059 attenuated the inhibitory effect of ezetimibe on the expression of p‐ERK1/2 and caveolin‐1. Taken together, these results showed that ezetimibe suppressed foam cell formation via the caveolin‐1/MAPK signalling pathway, suggesting that inhibition of foam cell formation might be a novel mechanism underlying the anti‐atherosclerotic effect of ezetimibe.